Primary ovarian non-Hodgkin’s lymphoma in a 1-year-old child: A rare case report (Indian Journal of Case Reports, 2020)
Primary ovarian non-Hodgkin’s lymphomas (NHLs) are extremely rare. The definitive diagnosis can be done only by correlation of the clinical, radiological and pathological findings. Secondary ovarian lymphomas as a part of systemic disease are well known. We report a case of primary NHL of the ovary in a 1-year-old female child with unilateral involvement. Ultrasonography revealed a large pelvic mass, without associated regional or distant lymphadenopathy. The diagnosis was established by histological study and subsequent immunohistochemistry of the excised tumor mass. The case is rare due to its primary nature and presentation in this age group. Prognosis of primary ovarian lymphoma is the same as that of other primary nodal lymphomas. We want to highlight the importance of considering this as a differential diagnosis of lower abdominal mass in appropriate clinicoradiological scenario.